Bacteriological Findings in Active Otitis Media with Perforated Tympanic Membrane - Muwafaq Ahmed Salih (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Discharge from the ear is one of the commonest symptoms of infections of the ear. It can arise in both adults and children from a number of sources, (External canal, Middle Ear, and Mastoid cavity). And may have a variety of aetiologies, but the most common causes were acute, and chronic otitis media with perforation of the tympanic membrane. Aim of Study: To evaluate the most common types of bacteria that found in a discharging ear, and to appreciate the most appropriate antibacterial drugs acting on these bacteria. Patient and Methods The present prospective study includes 200 patients presented with ear discharge to the department of otolaryngology in Sulaimani Teaching Hospital from July 2008 to July 2009 including age group ranging from 6m->40years from both sexes.Identification of bacteria was done by colonial appearance, gram stain and biochemical tests. Results :Of 200 patients with ear discharge the maximum age involved is >40 years, male to female ratio 1.01:1, most of the cases were chronic otitis media 154 (77%), and the commonest type of discharge were mucopurulent (31%) in which the most common type of pathogen was staph.epidermidis(18%). followed by klebsiella sp. (15%), and Pseudomonas.aeroginosa (11%). Acute otitis media constitute about 27% of cases in which the most common type of discharge was serous, and the bacteria was staph.aureus as a most common pathogen (31%), most of gram +ve bacteria are strongly sensitive to amikacin and gentamycin, all types of the cultured microorganisms were sensitive to ciprofloxacin. Conclusion: chronic otitis media is the most common cause of ear discharge (mucopurulent) in which the most common type of microorganism is staph.epidrmidis. and (purulent) type of discharge is pseudomonas.aerogenosa. while in acute otitis media the most common type of discharge is (serous) in which staph aureus is the most common type.